Research on carbon emission characteristics and accounting framework of the new electric power system - Zhang Xiaoxuan; Cong Pengwei; Wang Yu (E3S Web of Conferences, 2024)
This article analyzes the current status of carbon emission statistical accounting system construction both domestically and internationally, analyzes the six major trends in the changes in carbon emission characteristics of electricity under the construction of new power systems, and based on this, proposes a framework for carbon emission statistical accounting system under the new power system, providing basic support for improving electricity carbon emission accounting and carrying out carbon emission control.